Partial Rectangular Metric Spaces and Fixed Point Theorems. (29th January 2014) - Shukla, Satish
Abstract : The purpose of this paper is to introduce the concept of partial rectangular metric spaces as a generalization of rectangular metric and partial metric spaces. Some properties of partial rectangular metric spaces and some fixed point results for quasitype contraction in partial rectangular metric spaces are proved. Some examples are given to illustrate the observed results.